2020
DOI: 10.3390/microorganisms8101613
|View full text |Cite
|
Sign up to set email alerts
|

Mardivirus Infection and Persistence in Feathers of a Chicken Model Harboring a Local Autoimmune Response

Abstract: Herpesvirus of turkey (HVT) is commonly used as a vaccine to protect chickens against Marek’s disease. Following vaccination, HVT infects feathers where it can be detected in all chicken lines examined. Unlike the parental Brown line (BL), Smyth line (SL) chickens develop vitiligo, due to autoimmune destruction of melanocytes in feathers. Previous reports showed a strong inflammatory response in Smyth chickens’ feathers at vitiligo onset, that subsided once melanocytes were destroyed, and depigmentation was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Studies have shown that T lymphocytes, mainly cytotoxic CD8+ T cells, that infiltrate the edges of vitiligo lesions, mediate the elimination of MCs and play a necessary and sufficient role in the occurrence and development of vitiligo. While regulatory T cells (Tregs) maintain immune homeostasis and suppress inflammation, skin Resident Memory T (TRM) cells induce vitiligo relapse [14]. According to this theory, several kinds of mouse vitiligo models have been established.…”
Section: Mouse Models Of Vitiligomentioning
confidence: 99%
“…Studies have shown that T lymphocytes, mainly cytotoxic CD8+ T cells, that infiltrate the edges of vitiligo lesions, mediate the elimination of MCs and play a necessary and sufficient role in the occurrence and development of vitiligo. While regulatory T cells (Tregs) maintain immune homeostasis and suppress inflammation, skin Resident Memory T (TRM) cells induce vitiligo relapse [14]. According to this theory, several kinds of mouse vitiligo models have been established.…”
Section: Mouse Models Of Vitiligomentioning
confidence: 99%
“…Three contributions highlight the value of MDV infections in chickens as a model for human diseases. Erf et al used a Mardivirus in vivo model to gain new insights into vitiligo, a chronic autoimmune disorder [ 11 ]. A genomics study by Steep et al revealed that key somatic mutations in the Ikaros cancer driver gene can contribute to MDV-induced tumorigenesis.…”
mentioning
confidence: 99%